2022
DOI: 10.21203/rs.3.rs-1766575/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of Obesity in Early and Late Childhood Based on Growth Trajectory During Infancy

Abstract: Childhood obesity rates have reached epidemic levels with Mediterranean countries reporting among the highest numbers globally. Evidence suggests early life factors, including infant growth rate, increase the risk of obesity later in childhood. However, optimal rates of infant growth associated with lower future obesity risk remains undetermined. The study aim was to determine the optimal infant growth rate associated with a lower risk of childhood overweight and obesity. Perinatal and anthropometric data coll… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In a recently published article, the association between infancy growth rates and overweight/obesity in greek pre-school children (2 -5 years old) and adolescents (10 -12 years old) were analyzed. The authors demonstrated a positive association between rapid weight gain during infancy and overweight/obesity at pre-school years and adolescence, with statistical significance in the latter (4). In this study, infancy was defined as the first 6 months of life, which roughly corresponds to the suckling period in our mouse model.…”
Section: Discussionmentioning
confidence: 76%
“…In a recently published article, the association between infancy growth rates and overweight/obesity in greek pre-school children (2 -5 years old) and adolescents (10 -12 years old) were analyzed. The authors demonstrated a positive association between rapid weight gain during infancy and overweight/obesity at pre-school years and adolescence, with statistical significance in the latter (4). In this study, infancy was defined as the first 6 months of life, which roughly corresponds to the suckling period in our mouse model.…”
Section: Discussionmentioning
confidence: 76%